Analisis Kepatuhan Syariah pada Investasi Emas Kontemporer - Lubis, Arowadi; Haris, Abdul (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
The purpose of this research is two things. First, whether investment activities are under the nature of investment in Islam. Second, to investigate whether gold investment activities are following Islamic law, namely legal and lawful. An analytical method is the screening method, namely comparing the Islamic concept and the applied concept. The indicators are conformity with the concept of investment in Islam, the validity of the contract, characteristics of gold transactions that are following sharia, conformity with hoarding gold, and there is no price-fixing. The results of the analysis showed several findings. First, the Islamic investment concept different from the applied gold investment concept. Second, investment activities are trading and safekeeping gold which are legally valid. Third, in the gold savings account, there is a violation of sharia because the transaction is not a cash and the gold is fictitious. Fourth, if the activity of storing gold is to buy future needs, then it becomes halal. On the other hand, if there is no purpose for spending in the future, then it becomes haram. Fifth, there is a violation of the Shari'a in terms of price-fixing by a third party as a determinant of the price of gold.